General plenty : always and only the path to peace - Neuss, Mike (PerfCon, 2001)
A family clan gathers for the Thanksgiving holidy following September11. Over two extraordinary evenings, Uncle Al tell them of humanity's option for success, and the only real magic of our time that, for the first time in human history, it's possible.